WAMBAF – Good Practices for Ditch Network Maintenance to Protect Water Quality in the Baltic Sea Region - Finér, Leena; Čiuldienė, Dovilė; Lībieté, Zane; Lode, Elve; Nieminen, Mika; Pierzgalski, Edward; Ring, Eva; Strand, Lars; Sikström, Ulf (Luonnonvarakeskus, 2018)
These good practices for ditch network maintenance (DNM) were prepared within the WAMBAF project (Water Management in Baltic Forests); project period from 1.3.2016 to 28.2.2019, which was initiated to tackle the problems relating to water quality after forestry operations in the Baltic Sea Region. The main aim of these good practices for DNM to protect water quality is to give background information and an overview of available water protection measures that can be used in conjunction with DNM on peatlands and paludified mineral soils to reduce the export of suspended solids (SS), nitrogen (N), phosphorus (P), and methyl mercury (MeHg) within the Baltic Sea Region. The good practices for DNM also deal with the suitability of DNM for peatlands and paludified soils by presenting tradeoffs between its benefits and detrimental impacts on water quality, as well as the planning of water protection measures to avoid or reduce transport of SS and nutrients to the receiving water bodies. In this document, we (i) describe the aims of DNM and give an overview of the existing scientific knowledge of the effects of DNM on tree growth, soil properties, hydrology and soil hydraulics, and drainage water quality, (ii) present factors for assessing the suitability of DNM, and (iii) present the principles of DNM planning and water protection for the reduction of the exports of SS, N and P to the water bodies in the Baltic Sea Region.
Keywords: Baltic Sea Region; ditch cleaning; forest drainage; guidelines; nutrient leaching; suspended solids; water protection